2018
DOI: 10.17512/pjms.2018.18.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Italian Online Shoppers’ Preference of Cash on Delivery: Empirical Analysis

Abstract: In recent years, there is a significant expansion of online-shopping which creates the need for a thorough marketing analysis of online customer behavior. The study examines the factors influencing Italian online shoppers' preferences of a particular payment method, precisely, it investigates the use of cash-on-delivery as a preferred payment method among Italian online shoppers. We consider both the impact of online shopping trends of the population and the impact of the determinants affecting e-shop preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…This research has revealed that perceived security, privacy, and trust have a significant influence on the customers' intention to adopt a COD payment method. Further, this study found few important facts regarding the COD payment method such as an increase of the frequency of online shopping leads to a slight increase in using cash-ondelivery as a payment method, the more important the factor of the online seller's reputation is, the lower the likelihood of preference for a COD payment method and local origin of the online seller increases the preference COD payment method (Pencarelli, et al, 2018). Polasik & Fiszeder (2010) analyzed factors influencing the acceptance of the seven major payment methods by the polish managers of online shops and the results of this study demonstrated that a shop's strategy of using traditional and electronic distribution channels, preferences of online shop managers, the involvement in online auctions and cross-border sales have significant influences on its acceptance of particular payment methods.…”
Section: Cash On Delivery Services In the Global Contextmentioning
confidence: 78%
See 4 more Smart Citations
“…This research has revealed that perceived security, privacy, and trust have a significant influence on the customers' intention to adopt a COD payment method. Further, this study found few important facts regarding the COD payment method such as an increase of the frequency of online shopping leads to a slight increase in using cash-ondelivery as a payment method, the more important the factor of the online seller's reputation is, the lower the likelihood of preference for a COD payment method and local origin of the online seller increases the preference COD payment method (Pencarelli, et al, 2018). Polasik & Fiszeder (2010) analyzed factors influencing the acceptance of the seven major payment methods by the polish managers of online shops and the results of this study demonstrated that a shop's strategy of using traditional and electronic distribution channels, preferences of online shop managers, the involvement in online auctions and cross-border sales have significant influences on its acceptance of particular payment methods.…”
Section: Cash On Delivery Services In the Global Contextmentioning
confidence: 78%
“…All the major logistics and courier companies over the world serving direct end-customers through E-commerce deliveries consider cash on delivery management as a key transaction method that has sustained its popularity, notwithstanding multiple payment options gaining ground. "This is sometimes called "post-payment" system because the customer receives goods before making a payment" (Pencarelli, et al, 2018). It has been statistically proved that E-commerce stores that offer COD services attract more online buyers than the ones who are limited to online payment gateways (courier.lk, 2020).…”
Section: Cash On Delivery Methodsmentioning
confidence: 99%
See 3 more Smart Citations